2016
DOI: 10.1016/j.sbi.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Metallocofactor assembly for [FeFe]-hydrogenases

Abstract: Hydrogenases are a potential source of environmentally benign bioenergy, using complex cofactors to catalyze the reversible reduction of protons to form hydrogen. AddressesChemistry and the Institute for Life Sciences, University of Southampton, Highfield Campus, Southampton SO17 1BJ, UK.Corresponding author: Peter L. Roach (plr2@soton.ac.uk). AbstractHydrogenases are a potential source of environmentally benign bioenergy, using complex cofactors to catalyze the reversible reduction of protons to form hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…The original set of 650 sequences has now grown over 150-fold (not counting sequences from the large compilations of metagenomic data now coming available). Known functions reveal that RSS enzymes catalyze a dizzying array of disparate and essential chemistries that range from the formation of complex metal cofactors (Dinis, Wieckowski, & Roach, 2016) (e.g. the formation of the [FeFe]-hydrogenase metallocofactor in HydG (Pilet et al, 2009) and HydE (Nicolet et al, 2008)) to the formation of more than half of the over two dozen known organic cofactors (for example, biotin (Lotierzo, Tse Sum Bui, Florentin, Escalettes, & Marquet, 2005; Reyda, Dippold, Dotson, & Jarrett, 2008), lipoic acid (Cicchillo, Lee, et al, 2004; Miller et al, 2000), menaquinone (vitamin K) (Hiratsuka et al, 2008) and pyrroloquinonoline quinone (PQQ) (Barr et al, 2016; Puehringer, Metlitzky, & Schwarzenbacher, 2008)).…”
Section: Introduction: Overview Of the Radical Sam Superfamilymentioning
confidence: 99%
“…The original set of 650 sequences has now grown over 150-fold (not counting sequences from the large compilations of metagenomic data now coming available). Known functions reveal that RSS enzymes catalyze a dizzying array of disparate and essential chemistries that range from the formation of complex metal cofactors (Dinis, Wieckowski, & Roach, 2016) (e.g. the formation of the [FeFe]-hydrogenase metallocofactor in HydG (Pilet et al, 2009) and HydE (Nicolet et al, 2008)) to the formation of more than half of the over two dozen known organic cofactors (for example, biotin (Lotierzo, Tse Sum Bui, Florentin, Escalettes, & Marquet, 2005; Reyda, Dippold, Dotson, & Jarrett, 2008), lipoic acid (Cicchillo, Lee, et al, 2004; Miller et al, 2000), menaquinone (vitamin K) (Hiratsuka et al, 2008) and pyrroloquinonoline quinone (PQQ) (Barr et al, 2016; Puehringer, Metlitzky, & Schwarzenbacher, 2008)).…”
Section: Introduction: Overview Of the Radical Sam Superfamilymentioning
confidence: 99%
“…26,2831 Recent spectroscopic and structural work has shown that the accessory cluster site in HydG is occupied by a [4Fe-4S][(κ 3 -Cys)Fe] moiety that is proposed to be the site of Fe(CO) 2 (CN)Cys synthon formation, although the precise mechanistic details of DHG breakdown at this site require further clarification. 24,28,3236 …”
mentioning
confidence: 99%
“…These systems function similarly, but they are biochemically discrete. Additional systems have been described for building more complex Fe-S clusters such as those found in dinitrogenase reductases and hydrogenases (reviewed in references 14 and 15 ).…”
Section: Building Iron-sulfur Clustersmentioning
confidence: 99%